Fungigação utilizando gotejamento na cultura do tomate para o controle da pinta preta - Tolentino Júnior, João Batista (2008)
Tomato plants (var. Santa Clara) were cultivated inside greenhouse in vase. Fifty days after transplantation were inoculated with Alternaria solani and treated with 4 fungicides: azoxystrobin (8 g 100 L-1), difeconazol (50 mL 100 L-1), metiran+piraclostrobin (200 g 100 L-1) and tebuconazol (100 mL 100 L-1), in twos ways of application: conventional pulverization and drip chemigation. The treatment control did not receive fungicide application. Disease severity was evaluated by rating scale and expressed in area under the disease progress curve (AUDPC) and production factors, numbers, weight and diameter of fruits and yield. The experimental design was 4x2+1 with 8 replications, being each parcel formed by one plant in one vase. The disease severity was reduced 27% in comparison to control and did not observe significant difference between application methods. Azoxystrobin applied by fungigation reduced the area under the disease progress curve to 60.41 in comparison to the others fungicides that obtained 71.44; 74.93 and 75.33 for difeconazol, tebuconazol and metiran+piraclostrobin, respectively. The number of fruits did not differ significant between treatments. The mass and diameter of fruits were higher in treatments with fungicides than in treatment control and therewith yield was increased.